The effect of low-level laser irradiation on free radical processes in the mitochondrial fractions induced by the bisphenol A administration. - Borschovetska, Vira; Marchenko, Mykhailo; Ivantsiv, Vitalina (Scientific Herald of Chernivtsi University. Biology (Biological Systems)., 2021)
Bisphenol A (BPA), the xenoestrogen and plasticizer, can induce mitochondrial dysfunction via the shift in the balance between oxidants and antioxidants. Low-level laser irradiation may influence oxidative stress parameters by changing the activity of antioxidant enzymes and the production of ROS. Our study aimed to investigate the effect of low-level laser irradiation on oxidative stress parameters in hepatic mitochondrial fractions of rats under the conditions of BPA administration. The BPA was administered per os daily for 3 days at a dose of 50 mg/kg body weight. Low-level laser irradiation was performed after each or last administration of xenobiotic. The activity of antioxidant enzymes and the content of free radicals was spectrophotometrically determined in the mitochondrial fraction of the liver. Short-term BPA exposure results in the induction of free radical processes in hepatic mitochondria by the enhanced generation of O2• –and decreased activity of antioxidant enzymes. At the same time, low-level laser irradiation reduces the prooxidant effect of this xenobiotic in mitochondria by the enhancement of the antioxidant activity, which is primarily associated with conformational changes induced by a short-term increase in the temperature of light-absorbing biomolecules. This effect was observed only in the case of LLLI after BPA exposure.
Keywords: low-level laser irradiation; bisphenol A; antioxidant system; free radicals